Biology and chemical weed management of Cynanchum acutum L. - Bar, Oeri; Lati, Ran Nisim; Schäckermann, Jessica; Kapiluto, Omer; Spodek, Malkie; Gamliel, Abraham; Matzrafi, Maor (Frontiers in Agronomy, 2024)
Cynanchum acutum L. (Asclepiadaceae) is a perennial vine weed widespread in the Mediterranean region. In Israel, it is native to areas such as the Golan Heights, Galilee, and the northern Negev. Recently, its range has expanded to the Arava Valley in the southern part of Israel. In this study, we investigate the biology and phenology of C. acutum plants originating from both native and invasive populations. To achieve this, we utilized rhizomes from the invasive area in the southern region characterized by a hyper-arid desert climate (Yahel), and from the northern region characterized by a temperate climate (Gvat). Additionally, we examine chemical-based weed management approaches for controlling C. acutum. Rhizomes collected from the northern region showed higher emergence rates at temperatures between 15-30°C, whereas at 35°C, rhizomes from the southern region exhibited a higher emergence rate. Phenology experiments conducted simultaneously at southern and northern locations revealed that plants from the northern location flowered first at both sites. However, flowering initiation occurred ~20 days earlier on average when plants from both populations were grown at the southern site. Pre-emergence herbicide treatments using indaziflam and pyroxasulfone were effective in inhibiting C. acutum root formation. According to the percentage of emergence, pendimethalin showed higher emergence (93% and 100%) in comparison to indaziflam (10% and 93%) and pyroxasulfone (72% and 70%) (2020 and 2021, respectively). Treatments including the herbicide fluroxypyr, as well as the treatment of glyphosate + saflufenacil + surfactant were highly effective in controlling C. acutum plants. These results offer valuable insights into effective weed management strategies for addressing C. acutum infestations. Moreover, our findings underscore the remarkable plasticity of this species and shed light on how populations originating from diverse habitats may have adapted to distinct environmental conditions.